A systematic review of the effectiveness of occupational health and safety training - Lynda S Robson; Carol M Stephenson; Paul A Schulte; Benjamin C Amick; Emma L Irvin; Donald E Eggerth; Stella Chan; Amber R Bielecky; Anna M Wang; Terri L Heidotting; Robert H Peters; Judith A Clarke; et al. (Nordic Association of Occupational Safety and Health (NOROSH), 2012)
OBJECTIVES: Training is regarded as an important component of occupational health and safety (OHS) programs. This paper primarily addresses whether OHS training has a beneficial effect on workers. The paper also examines whether higher engagement OHS training has a greater effect than lower engagement training. METHODS: Ten bibliographic databases were searched for pre-post randomized trial studies published in journals between 1996 and November 2007. Training interventions were included if they were delivered to workers and were concerned with primary prevention of occupational illness or injury. The methodological quality of each relevant study was assessed and data was extracted. The impacts of OHS training in each study were summarized by calculating the standardized mean differences. The strength of the evidence on training's effectiveness was assessed for (i) knowledge, (ii) attitudes and beliefs, (iIi) behaviors, and (iv) health using the US Centers for Disease Control and Prevention's Guide to Community Preventive Services, a qualitative evidence synthesis method. RESULTS: Twenty-two studies met the relevance criteria of the review. They involved a variety of study populations, occupational hazards, and types of training. Strong evidence was found for the effectiveness of training on worker OHS behaviors, but insufficient evidence was found of its effectiveness on health (ie, symptoms, injuries, illnesses). CONCLUSIONS: The review team recommends that workplaces continue to deliver OHS training to employees because training positively affects worker practices. However, large impacts of training on health cannot be expected, based on research evidence.